State Programs to Counter the Corona Crisis — an Option for Climate Protection? - Erik Gawel; Paul Lehmann (Wirtschaftsdienst)
Abstract Public measures to combat the coronavirus pandemic have led to a severe economic crisis. In order to cope with this crisis, many expect strong state intervention. Governments across the world have pledged billions of euros for extensive recovery programs. But how ‘green’ should these recovery programs be? This article evaluates Germany’s initial policy proposals and decisions.